Gambaran Pengetahuan Pengelolaan ASI pada Ibu Menyusui di PMB SR Kecamatan Jabung Kabupaten Malang - Syifa Maulida; Jenny J.S Sondakh; Ika Yudianti (Poltekkes Kemenkes Malang, 2019)
The achievement of low exclusive breastfeeding is a sign that awareness of breastfeeding mothers in providing breastfeeding still needs to be improved. In the practice of exclusive breastfeeding, it was found that breastfeeding mothers tended to be reluctant to give breast milk to their babies at the beginning of the lactation process and discard their breast milk. The impact continues if the breast is not pumped, it will reduce the breast milk production and finally produce little breast milk. So when the baby age increases, breast milk production decreases and there is no supply of breast milk in the mother breast. This research aimed to show the description of knowledge about breast milk management in breastfeeding mothers in PMB Jabung Subdistrict Malang Regency. This research used quantitative descriptive design with survey method. Total of breast feeding mothers in PMB Jabung Subdistrict Malang Regency were 60 and the samples of study were 52 people with purposive sampling technique. Instruments in this study used a valid questionnaire to identify the level of knowledge about breast milk management technique. This research presented in tabular and narrative. Data analysis using descriptive analysis. The results showed that most of the respondents that is as much 40,4 percent had the lack knowledge about breast milk management, the others that is as much 38,5 percent and 21,1 percent had enough and good level of knowledge about breast milk management. Based on the result of this research most breastfeeding mothers never get counseling about breast milk management.